AN APPLICATION OF APAPRIHA ̅NIYADHAMMA PRINCIPLE OF THE MEMBERS OF THE ARTS AND CRAFTS PROMOTION CENTER IN BAN KUT NA KHAM, CHAROEN SIN DISTRICT, SAKON NAKORN PROVINCE - Seelawong, Phramaha Sanguan (Journal of MCU Nakhondhat, 2021)
This article discusses the application of the Apaprih Niyadhamma Principle of the members in the Arts and Crafts Promotion Center, Ban Kut Nakham, Chareon Sin District, Sakon Nakorn Province. of this research were; 1) to study the life styles of community in Ban Kut Na Kham, Charoen Sin District, Sakon Nakorn Province 2) to study the in accordance with the Apaprih Niyadhamma principle of the members of the Arts and Crafts y Promotion Center of Ban Kut Nakham and 3) to study an application of the Apaprih Niyadhamma Principle of the members in the Arts and Crafts Promotion Center, Ban Kut Nakham, Chareon Sin District, Sakon Nakorn Province. This research is the qualitative research by studying the data from the documents and field study for collecting the data from interviewing. The results are as follows. The results of research were found the application of the Apaprih Niyadhamma Principle of the members in the Arts and Crafts Promotion Center, Ban Kut Nakham, Chareon Sin District, Sakon Nakorn Province. that the life styles of the community in Ban Kut Na Kham, Chareon Sin District, Sakon Nakorn Province showing that the majority of the members of the Arts and Crafts promotion was the agriculturists by planting the agricultural plants as main points such as to feat the domestic animals in the families, not to be the farms, to have the water sources called the basin of Hauy Nok Khaow. It has been the water source for life. The people’s life styles in Ban Kut Na Kham is the sufficient life style and searching for the knowledge by the members in the Arts and Crafts Promotion Center, who develop their own professional crafts plus the Isan cultures. To create the art works plus the creative thought in inventing the various works such as Maithai weaving clothes, Ceramic dolls, ceramic vessels, craft works and Khon cardigans makes the Kut Na Kham village satisfied from people in various locations.